Implementation of Murabaha Contracts in Implant Financing at Bank Mandiri Syariah Subbranch Sengkang - Awaliyah, Dien Putri; Trimulato, Trimulato; Nuringsih, Nuringsih; Lismawati, Lismawati; Agussalim, Agussalim (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2024)
This study aims to determine the application of Murabahah contracts in implant financing at Bank Syariah Mandiri Sub-branch Sengkang and the customer's perspective on implementing the contract. The benefit of this research is that it can add insight and knowledge in the field of Sharia banking and can be used as a scientific contribution and increase knowledge, especially for banks, it can be used as a reference in improving management performance and improving the quality and quality of service to the community. This research uses qualitative methods. with an approach through interviews, observation, and documentation to parties related to Bank Syariah Mandiri Sub-branch Sengkang. The analysis technique used in this study is descriptive analysis, a way to process data into information so that the characteristics of the data can be understood and useful for solving problems and describing the situation or event of a problem to be solved. The results of this study are the application of a Murabahah contract, namely using Bank Syariah Mandiri Sub-branch Sengkang entering a Murabahah agreement with the customer, and at the same time delegating (wakalah contract) to the customer to buy the goods needed by reporting the purchase receipt to the bank.